Análisis de la formación de actitudes sobre la marca - Brito, Jorge G. (2018)
Prestigious marketing texts refer to the importance of brand building, which implies a study of the psychological, humanistic social profile of consumers based on loyalty, the tastes and preferences of consumers whose variables are an essential part in the creation of models the same ones that provide us with a theoretical abstraction towards reality. On the other hand, there is another theoretical reflection that determines the incidence of this type of variables in the formation of the attitudes of Guayaquil consumers on brands, which in turn stimulates investment and the generation of employment sources, being beneficial for the redistribution of wealth, taking into account current market conditions. In this article, a proposal for the formation of attitudes about the brandin the city of Guayaquil is tested for the Ecuadorian case and technical parameters are established that allow the main objective of the presentation. A methodology based on the Theory of Reasoned Action "Model based on human behavior" developed by MartinFishbein and Icek Ajzen (1975, 1980) is proposed. Finally, the criteria formulated solidly on the human behavior applied to the branding are raised, based on this principle, the quantitative validation of the model with the classified brands and with their respective categories would be immediately carried out.